Paris at war, 1939-1944 - Drake, David, 1946- (The Belknap Press of Harvard University Press, 2015)
Chronicles the lives of ordinary Parisians during World War II, from September 1939 when France went to war with Nazi Germany to liberation in August 1944. Relive the fearful exodus from the city as the German army neared the capital, the relief and disgust felt when the armistice was signed, and the hardships and deprivations under Occupation.